EUROPIUM AND DYSPROSIUM IONS CO-DOPED WHITE LIGHT LUMINESCENCE MAGNESIUM SULFOBORATE GLASSES FOR WHITE LEDS - DALHATU, SADIQ ABUBAKAR; BABALE, AUWALU; ALKALI, BABANGIDA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
To develop a new luminescence property of europium and dysprosium ions co-doped Magnesium sulfoborate glasses, and to apply it for white LEDs. Europium and dysprosium codoped Magnesium sulfoborate glasses are prepared by conventional melt quench technique and their excitation and luminescence characteristic were studied. The samples were characterized using X-Ray Diffraction (XRD) and emission spectra by exciting the glass at 350 nm. XRD confirms the amorphous nature of the prepared samples. A combination of blue, green, yellow and red emission bands was shown for these glasses, and white light emission could be observed under UV light excitation. These results indicate that Europium and dysprosium codoped magnesium sulfoborate glasses could be a potential candidate for white LEDs with excitation of a 360 nm near UV LED chip.